Rhizospheric Bacillus spp. Rescues Plant Growth Under Salinity Stress via Regulating Gene Expression, Endogenous Hormones, and Antioxidant System of Oryza sativa L - Khan, Muhammad Aaqil; Hamayun, Muhammad; Asaf, Sajjad; Khan, Murtaza; Yun, Byung-Wook; Kang, Sang-Mo; Lee, In-Jung (Frontiers in Plant Science, 2021)
Salinity has drastically reduced crop yields and harmed the global agricultural industry. We isolated 55 bacterial strains from plants inhabiting the coastal sand dunes of Pohang, Korea. A screening bioassay showed that 14 of the bacterial isolates secreted indole-3-acetic acid, 12 isolates were capable of exopolysaccharide production and phosphate solubilization, and 10 isolates secreted siderophores. Based on our preliminary screening, 11 bacterial isolates were tested for salinity tolerance on Luria–Bertani media supplemented with 0, 50, 100, 150mM of NaCl. Three bacterial isolates, ALT11, ALT12, and ALT30, had the best tolerance against elevated NaCl levels and were selected for further study. Inoculation of the selected bacterial isolates significantly enhanced rice growth attributes viz. shoot length (22.8%–42.2%), root length (28.18%–59%), fresh biomass (44.7%–66.41%), dry biomass (85%–90%), chlorophyll content (18.30%–36.15%), Chl a (29.02%–60.87%), Chl b (30.86%–64.51%), and carotenoid content (26.86%–70%) under elevated salt stress of 70 and 140 mM. Furthermore, a decrease in the endogenous ABA content (27.9%–23%) and endogenous salicylic acid levels (11.70%–69.19%) was observed in inoculated plants. Antioxidant analysis revealed an increase in total protein (42.57%–68.26%), whereas it revealed a decrease in PPO (24.63%–34.57%), GSH (25.53%–24.91%), SOA (13.88%–18.67%), and LPO levels (15.96%–26.06%) of bacterial-inoculated plants. Moreover, an increase in CAT (26%–33.04%), POD (59.55%–78%), SOD (13.58%–27.77%), and APX (5.76%–22.74%) activity was observed. Additionally, ICP analysis showed a decline in Na+ content (24.11% and 30.60%) and an increase in K+ (23.14% and 15.45%) and Mg+ (2.82% and 18.74%) under elevated salt stress. OsNHX1 gene expression was downregulated (0.3 folds and 4.1 folds), whereas the gene expression of OsPIN1A, OsCATA, and OsAPX1 was upregulated by a 7–17-fold in bacterial-inoculated rice plants. It was concluded that the selected bacterial isolates, ALT11, ALT12, and ALT30, mitigated the adverse effects of salt stress on rice growth and can be used as climate smart agricultural tools in ecofriendly agricultural practices.